Handbook of pediatric and neonatal transport medicine (Hanley & Belfus, Inc, 2002)
Univ. of Illinois, Chicago. Presents practical information for developing an effective organization for the transport of infants and children. Discusses all forms of transportation and presents strategies for handling a wide array of problems. Softcover. DNLM: Patient Transfer.